PENGUATAN KETAHANAN PANGAN KELUARGA MELALUI IMPLEMENTASI EKONOMI BIRU SKALA RUMAH TANGGA PADA KELOMPOK DASA WISMA ORONG PUKEN DI DESA DUN TANA - Nawastuti, Dati (POLITEKNIK LP3I JAKARTA, 2026)
Household food security is a strategic issue in rural development, particularly in island and remote areas such as Dun Tana Village, Titehena Sub-district, East Flores Regency, East Nusa Tenggara Province. This study aims to analyze the implementation of the blue economy at the household scale and its role in strengthening family food security through Dasa Wisma groups. The research employed a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation involving members of Dasa Wisma groups, group coordinators, and relevant village stakeholders. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results indicate that the implementation of the household-scale blue economy has been carried out through the utilization of home gardens, management of local resources, and simple household waste reduction practices. These activities contribute to increased availability and diversity of food for some households; however, the impact has not been evenly experienced by all Dasa Wisma members. Differences in land size, participation levels, technical knowledge, and dependence on seasonal and environmental factors are the main determinants influencing household food security outcomes. From an economic perspective, the impact remains limited, as production outputs are primarily used for household consumption and have not yet been oriented toward market-based activities. This study concludes that the household-scale blue economy has the potential to strengthen family food security and women’s empowerment, but it requires capacity building, continuous assistance, and integration with village policies to ensure more equitable and sustainable benefits.